Molecular chaperone heat shock protein 70 inhibitors suppress conditioned place preference induced by morphine exposure in male rats. (2nd March 2022) - Wei, Shoupeng; Li, Yu‐ling; Gong, Qi; Liang, Hui; Bernardi, Rick E.; Liang, Jian‐hui
Abstract: Previous studies have indicated a role for molecular chaperone heat shock protein 70 (Hsp70) in the development of behavioural sensitization to morphine in rodents, suggesting that Hsp70 expression following morphine exposure is involved in molecular changes that may underlie addiction vulnerability. The current study was carried out to investigate the role of Hsp70 in the positive reinforcing properties of morphine using conditioned place preference (CPP) in male rats. An unbiased CPP procedure of three phases (pre‐conditioning: d1–d3; conditioning: d4–d6; and testing: d7) was used. During the conditioning phase, morphine injections (5 mg/kg, subcutaneously) were administered to induce significant place preference. To explore the effect of Hsp70 on the development and expression of morphine CPP, Hsp70 inhibitors (PES, KNK437 and methylene blue) were administered into the lateral ventricle prior to either morphine conditioning sessions or a morphine challenge on the test day. Furthermore, Hsp70 expression within the mesocorticolimbic system was measured after the treatment with KNK437, a transcriptional inhibitor. We found that PES and KNK437, respectively, injected intracerebroventricularly dose‐dependently attenuated both the development and expression of morphine CPP. Methylene blue treatment demonstrated an attenuation of the development, but had no effect on the expression of morphine CPP. Following KNK437 treatment, Hsp70 expression was significantly inhibited in the shell of nucleus accumbens (NAc) during both the development and expression of morphine CPP. The findings suggest that Hsp70 in the NAc shell plays an important role in the reinforcing effects of morphine and may be involved in the development of morphine dependence. Abstract : Hsp70 inhibitors, PES and KNK437, respectively, attenuated morphine CPP during both the development and expression in a dose‐dependent manner. Methylene blue treatment demonstrated an attenuation of the development but had no effect on the expression of morphine CPP. KNK437 treatment significantly decreased Hsp70 expression in the NAc shell, and the Hsp70 expression level had a good correlation with the CPP score during the development and expression of morphine CPP.